Behavioral and organizational variables affecting the success of ABC success in China - Fei, Z.Y.; Isa, C.R. (Academic Journals, 2010)
In today's advanced manufacturing environment increases the need for more accurate costing information. However, traditional volume-based costing system leads to cost information distortion. Activity-Based Costing (ABC) was introduced to address the shortcomings of traditional volume-based costing system. Due to its abilities to provide more accurate costing information for strategic decision, ABC has attracted the attention of both practitioners and researchers. Prior research findings indicated that in western countries, the main factors influencing the success of ABC were organizational factors, such as top management support, adequate resources, training and so on. Chinese firms are also motivated by current competitive environment to adopt ABC system to trace overhead cost. However, little research has been done in Chinese context and it is necessary to examine whether ABC could be implemented successfully in China. This paper replicates Shields's (1995) framework to examine the effect of behavioral and organizational variables on the ABC success implementation by using a sample of 106 Chinese manufacturing firms. The result shows that top management support significantly influences the ABC success implementation. The findings of this study also provide implication for the implementation of ABC for Chinese manufacturing firms.